Preparations and properties of ionic liquid-assisted electrospun biodegradable polymer fibers - Shamsuri, Ahmad Adlie; Abdan, Khalina; Md. Jamil, Siti Nurul Ain (MDPI, 2022)
Enhanced awareness of the environment and environmental conservation has inspired researchers to search for replacements for the use of volatile organic compounds in the processing of polymers. Recently, ionic liquids have been utilized as solvents for solvating natural and synthetic biodegradable polymers since they are non-volatile, recyclable, and non-flammable. They have also been utilized to prepare electrospun fibers from biodegradable polymers. In this concise review, examples of natural and synthetic biodegradable polymers that are generally employed as materials for the preparation of electrospun fibers are shown. In addition, examples of ionic liquids that are utilized in the electrospinning of biodegradable polymers are also displayed. Furthermore, the preparations of biodegradable polymer electrospinning solutions utilizing ionic liquids are demonstrated. Additionally, the properties of electrospun biodegradable polymer fibers assisted by different ionic liquids are also concisely reviewed. Besides this, the information acquired from this review provides a much deeper understanding of the preparation of electrospinning solutions and the essential properties of electrospun biodegradable polymer fibers. In summary, this concise review discovered that different functions (solvent or additive) of ionic liquids could provide distinct properties to electrospun fibers.